EFFECT OF DODECANOL ON MIXED NONIONIC AND NONIONIC/ANIONIC SURFACTANT ADSORPTION AT THE AIR-WATER-INTERFACE - Staples, E; Thompson, L; Tucker, I; Penfold, J (1994)
Neutron reflection has been used to investigate the adsorption of mixed nonionic surfactant and nonionic/ anionic surfactant mixtures containing dodecanol, at the air/water interface. The measurements clearly demonstrate the preferential adsorption of the more surface active shorter ethylene oxide nonionic surfactants, particularly of dodecanol. The usual trend for the more surface active components to decrease their presence in the surface layer as the total surfactant concentration increases is not observed for dodecanol. This results from the occurrence of unfavorable micellar geometries in mixtures containing dodecanol which control adsorption through their effect on monomer concentration. Regular solution theory cannot be used to describe the behavior of these systems. © 1994 American Chemical Society.